arc-dependent thermal regulation and extragenic suppression of the Escherichia coli cytochrome d operon. - Wall, D (1992)
In a screen for Escherichia coli genes whose products are required for high-temperature growth, we identified and characterized a mini-Tn10 insertion that allows the formation of wild-type-size colonies at 30 degrees C but results in microcolony formation at 36 degrees C and above (Ts- phenotype). Mapping, molecular cloning, and DNA sequencing analyses showed that the mini-Tn10 insertion resides in the cydB gene, the distal gene of the cydAB operon (cytochrome d). The Ts- growth phenotype was also shown to be associated with previously described cyd alleles. In addition, all cyd mutants were found to be extremely sensitive to hydrogen peroxide. Northern (RNA) blot analysis showed that cyd-specific mRNA levels accumulate following a shift to high temperature. Interestingly, this heat shock induction of the cyd operon was not affected in an rpoH delta background but was totally absent in an arcA or arcB mutant background. Extragenic suppressors of the Cyd Ts- phenotype are found at approximately 10(-3). Two extragenic suppressors were shown to be null alleles in either arcA or arcB. One interpretation of our results is that in the absence of ArcA or ArcB, which are required for the repression of the cyo operon (cytochrome o), elevated levels of Cyo are produced, thus compensating for the missing cytochrome d function. Consistent with this interpretation, the presence of the cyo gene on a multicopy plasmid suppressed the Ts- and hydrogen peroxide-sensitive phenotypes of cyd mutants.